A study on the holistic efficacy of different Radix Aconiti Preparata for treating rheumatic arthritis in rats based on the urinary metabonomic method using UPLC-Q-TOF-HDMS. Issue 15 (31st March 2016) - Jia, Fei; Xu, Tengfei; Qi, Yao; Liu, Shu; Pi, Zifeng; Song, Fengrui; Liu, Zhiqiang
Abstract : 15 potential biomarkers related to the efficacy of Radix Aconiti Preparata in adjuvant-induced arthritis rats had been identified by UPLC-Q-TOF-MS in urine, and they are mainly involved in four metabolic pathways. Abstract : Quality control of processed Radix Aconiti with toxicity and clinical therapeutic efficacy is very important since it is a widely used traditional herbal medicine with both therapeutic and highly toxic activities. However, until now the existing quality control methods have only been able to assess the toxicity of the different Radix Aconiti Preparata, but could not evaluate their clinical efficacy and clarify their precise mechanism of action. In this study, a urinary metabonomic study using UPLC-Q-TOF-HDMS combined with pharmacodynamics was performed for the first time to assess the holistic efficacy and to explore the potential mechanism of the different Radix Aconiti Preparata for treating rheumatic arthritis (RA) in rats. High pressure steamed Radix Aconiti Preparata (SRAP) that was steamed for one hour and boiled Radix Aconiti Preparata (BRAP) that was boiled for six hours were selected as representatives of different Radix Aconiti preparata . As a result, both SRAP and BRAP showed good effects on treating RA from the integrated evaluation by histological results, biochemical parameters and pattern recognition analysis. Meanwhile, a metabonomic investigation was conducted to study the mechanism of the SRAP and BRAP for treating RA. Multivariate statistical analyses such as OPLS-DA were used to identify potential biomarkers in urine. As a result, fifteen potential biomarkers have been found by comparison with the model and the Radix Aconiti Preparata treatment groups. The potential biomarkers mainly affect four metabolic pathways, including phenylalanine metabolism, tryptophan metabolism, fatty acid metabolism, and arginine and proline metabolism. This work is helpful to evaluate the clinical efficacy of Radix Aconiti Preparata and clarify their precise mechanism of action for the treatment of arthritis.